Revitalizing Higher Vocational Education in Yunnan, China Through Curriculum Redesign, Industry Partnerships, and Professional Development - Cheng, Yu; Zhang, Lei; Chouykerd, Prateep (ASEAN Journal of Education, 2025)
Higher vocational education plays a crucial role in equipping individuals with practical skills and knowledge for successful transitions into the workforce. However, ensuring the effectiveness and relevance of higher vocational education programs requires continuous evaluation and alignment with industry needs. This study aims to: (1) assess the current alignment of vocational education programs with industry-demanded skills, (2) examine professional development opportunities for instructors to enhance their knowledge and teaching methodologies, and (3) propose strategies for curriculum redesign, industry engagement, and professional development. Through surveys, and interviews, the research identifies mismatches between curricula and industry needs, assesses instructor training programs, and provides recommendations for revitalizing vocational education in Yunnan, China. The study surveyed a sample of 300 students and 100 instructors from public higher vocational colleges in Yunnan China, and 383 effective responses were retrieved. The samples were selected using stratified random sampling to ensure representation across different academic programs and levels. The research findings suggest that higher vocational education programs and their alignment with industry skill requirements are generally perceived positively by participants. However, there are areas with room for improvement, particularly in industry collaborations and addressing the variability in opinions regarding certain aspects of these programs. The correlation analysis indicates a strong positive relationship between the curriculum and students’ competencies, a strong positive relationship between the curriculum and professional development, and a strong positive relationship between industry collaborations and professional development.